Study of Normal Ranges of Radial and Ulnar Deviation among Female Medical Students (Journal of Nobel Medical College, 2025)
Background: Assessment of joint mobility is a fundamental component of the physical examination of the upper extremities. Accurate measurement of wrist movement helps clinicians evaluate joint laxity, functional capacity, and subtle variations in musculoskeletal structure. Radial and ulnar deviations, in particular, play an important role in activities requiring precision and dexterity, making their evaluation essential in clinical practice, rehabilitation, and research.Materials and Methods: This cross-sectional, descriptive study included 100 healthy female undergraduate Medical students of NMCTH, participants aged 18–24 years with normal wrist skeletal structure. Radial and ulnar deviations of both wrists were measured using a standard universal goniometer following established procedures.Results: The overall range of motion (ROM) across all four movements was comparable, averaging between 39° and 41°. Mean radial deviation was 38.76° ± 11.32° in the right hand and 41.18° ± 10.21° in the left hand. Mean ulnar deviation measured 39.84° ± 11.27° on the right and 40.46° ± 10.86° on the left. ROM values were consistently higher in the left wrist for both movements.Conclusion: This study demonstrates slightly greater wrist mobility on the left side compared to the right for both radial and ulnar deviations. No significant difference was observed between radial and ulnar deviation ranges themselves. Reduced mobility of the right wrist in predominantly right-handed individuals may reflect early functional strain or mild degenerative changes affecting the joint and surrounding ligaments.